TREN DRAMATURGI KAMPANYE PEMILU 2024 DI INSTAGRAM - Moekahar, Fatmawati; Syafhendry, Syafhendry; Hardiyanti, Fitri; Sunardi, Sunardi; Rafida, Norhayati (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Social media has become an important campaign medium for politicians. The politician behaves depending on his social role in a particular situation. In the dramaturgy by Erving Goffman, this is said to be a form of collaborative manufacturing that politicians will prepare for every event of social interaction. The aim of this article is to explore dramaturgy trends of presidential candidates in the 2024 election campaign on Instagram. Identify trends in the use of symbols and language used in interactions on Instagram during the election campaign. The method used is qualitative with an interpretive paradigm. The research period spans the 2024 election campaign period (November 28, 2023-February 10, 2024). Data was collected by an Instagram scrapper, coding, content categorization and interpretation of specific themes. The research results found that there were five categories of theme trends, namely: religious, social, family, nationalist and campaign programs. The synergy of the five themes becomes an integral part of forming the candidate’s front stage as a campaign action to influence the public. Instagram has become a front stage to display a positive image of candidates and impress the public in order to show their best side.